Demonstrating your clinical competence in respiratory disease, diabetes, and dermatology - Higgs, Jane; Chambers, Ruth, 1952-; Wakley, Gill; Pullan, Alistair (CRC Press, 2018)
Evidence-based medicine draws on terminology used in biostatistics epidemiology health economics philosophy ethics logic and the social sciences. In this unique compendium the author defines the common terms used in evidence-based medicine and provides useful notes and references to help the reader understand this terminology and explore further if necessary. The book explains statistical formulae commonly used in evidence-based medicine. It is ideal for doctors nurses and pharmacists who are not familiar with statistical terms and statisticians and health economists who are not familiar with pharmaceutical or clinical terminology. The definitions explanatory notes and references are clear and easily understandable.- Resumé vydavatel
First published 2005 by Radcliffe Publishing.
Keywords: ošetřovatelství; profesní kompetence; primární péče; nemoci dýchacích cest; diabetes mellitus; dermatologie; nursing; vocational qualifications; primary care; airways diseases; dermatology; elektronické knihy; příručky; případové studie; electronic books; handbooks and manuals; case studies